Japanese Management in Change: The Impact of Globalization and Market Principles - Kambayashi, Norio (Springer, 2015)
Following the burst of the “economic bubble” in the 1990s, many Japanese companies were required to reform their management systems. Changes in corporate governance were widely discussed during that decade in studies on “Japanese management.” These discussions have resulted in little progress, however, since Americanization became the dominant discourse concerning governance and the management system. There have been few studies conducted from an academic point of view on the internal aspects of organizations that practice traditional Japanese management theory.